Pitaya: a potential plant resource of citramalic acid. Issue 1 (1st January 2020) - Wu, Yawei; Xu, Juan; Shi, Meiyan; Han, Xiumei; Li, Wenyun; Zhang, Xingwu; Wen, Xiaopeng
ABSTRACT: Citramalic acid can reduce facial skin wrinkle of people and gives a promising usage in the fields of medicine and cosmetics, however, it has been detected in limited plants and the content were much low so far. Therefore, it is necessary to discover new plants that is rich in citramalic acid. Currently, qualitative and quantitative characterization of citramalic acid in pitaya were performed. The results demonstrated that citramalic acid was the dominant organic acid in pitaya fruit, accounting for 7.56–71.42% of total acid. The maximal concentration was up to 12.90 and 12.82 mg/g DW in pulp and peel, respectively, which were much higher than that in other plants reported. Consequently, our results manifested an abundant accumulation of citramalic acid in pitaya pulp as well as peel, and indicated that pitaya fruits might be used as a plant resource of citramalic acid.